Antiplasmodial Securinega alkaloids from Phyllanthus fraternus: Discovery of natural (+)-allonorsecurinine. Issue 38 (20th September 2017) - Komlaga, Gustav; Genta-Jouve, Grégory; Cojean, Sandrine; Dickson, Rita A.; Mensah, Merlin L.K.; Loiseau, Philippe M.; Champy, Pierre; Beniddir, Mehdi A.
Graphical abstract: Highlights: A new Securinega alkaloid was isolated from Phyllanthus fraternus . (+)-Allonorsecurinine constitutes an example of synthesized first, then isolated. Its absolute configuration was determined using optical rotation and NMR. The isolated compounds exhibited antiplasmodial activities in the micromolar range. Abstract: The chemical investigation of the antimalarial plant Phyllanthus fraternus G. L. Webster (Phyllanthaceae) resulted in the discovery of the Securinega alkaloid (+)-allonorsecurinine (1 ), previously reported as a synthetic compound, together with the known ent -norsecurinine (2 ), nirurine (3 ), bubbialine (4 ), epibubbialine (5 ) and the lignan phyllanthin (6 ). The structure and absolute configuration of the new compound were elucidated on the basis of extensive spectroscopic analysis, optical rotation, and GIAO NMR shift calculation followed by CP3 analysis. The antiplasmodial activity of these compounds was evaluated against chloroquine-resistant (W2) and -sensitive (3D7) strains of Plasmodium falciparum . Among them, ent -norsecurinine (2 ) and (+)-allonorsecurinine (1 ) showed the strongest activity (IC50 : 1.14 ± 0.32 and 2.57 ± 0.53 µM) respectively, against W2 but one of the weakest against 3D7.